The Effects of Vocabulary Learning Gamification on Students’ Vocabulary Development - Syauqi Yasfin Osadhi (Retain: Journal of Research in English Language Teaching, 2024)
In the study of foreign language like English, vocabulary plays a vital role in it. However, the most learners skipped this vital part due to monotonous repetitions of new words or phrases. This study investigates the effectiveness of Gimkit, a gamified learning platform, in improving vocabulary development. The primary objective was to determine whether Gimkit could significantly enhance students’ vocabulary development compared to conventional learning. An experimental research design involved two classes of eighth-grade students’ from SMPN 46 Surabaya: experimental group used Gimkit and control group used conventional learning (no treatment). A post-test measured vocabulary improvements. Data were collected using pre-test and post-test multiple-choice questions via Google Forms, with reliability and validity checks. Statistical analysis compared the two groups' performance, showing significant vocabulary improvement in the Gimkit group. This supports the idea that Gimkit makes learning more engaging and effective. However, the study had limitations like focusing only on specific vocabulary types and having limited sessions. Future research should explore more features of gamified tools like Gimkit. In conclusion, Gimkit is an effective tool for vocabulary improvement. Teachers should consider using gamified learning to boost engagement and outcomes. Further research should look into similar tools across different subjects and grades.